BIM-based integrated management workflow design for schedule and cost planning of building fabric maintenance - Chen, Chao; Tang, Llewellyn (Elsevier, 2019)
The operation and maintenance (O&M) is the longest and costliest phase during the entire building lifecycle. In recent decades, with the rapidly increasing costs of new constructions, the effective maintenance has become more important to the existing buildings, particularly to their fabric components, which include both architectural and structural items for maintaining physical characteristics and ensuring normal performance of the existing building over its lifecycle. However, building maintenance costs are also increasing dramatically and this situation mainly results from the delay of maintenance work due to inefficient maintenance planning for the facility management purpose. The inefficient maintenance planning is caused due to lack of effective methods and techniques for predicting the uncertainties including schedule and costs during the maintenance stage. Therefore, this paper proposes an innovative management workflow design which integrates Building Information Modelling (BIM) with digital programming to implement efficient schedule and cost planning of building fabric maintenance. Through this BIM-based workflow design, the knowledge gap between maintenance theories and practical maintenance management can be narrowed by a consistent and sustainable building information flow, which is highly linked with the design and construction phase. This study makes a contribution to integrating the traditional maintenance management with digital technologies to improve the management performance and maintenance efficiency of the O&M phase in the future.